Community Service: Safe, Effective, and Beneficial Skincare Counseling for Kalam Kudus II Jakarta High School Students - Sukmawati Tansil Tan; Yohanes Firmansyah; Alexander Halim Santoso; Ernawati Ernawati; Noer Saelan Tadjudin; Sari Mariyati Dewi Nataprawira; Susy Olivia Lontoh; Hendsun Hendsun; Fendy Wellen; Jeffry Luwito; Valeria Saputra; Stanley Surya Cahyadi; Muhamad Rizki Nanda F; Vonny Veronica Jap; Brigita Anasthasia Myra Nailulu (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2022)
Teenagers with inadequate knowledge about cosmetics are more likely to use harmful or unlawful goods. Students at SMA Kalam Kudus II Jakarta have never received instruction on the selection and application of beauty products. This counseling session is anticipated to raise the SMA Kalam Kudus II Jakarta students' awareness of the importance of utilizing adolescent-appropriate and safe skin care products and how to select them. This counseling procedure is conducted offline for counseling participants at Kalam Kudus II Jakarta High School. The given counseling material addresses a variety of adolescent skin conditions, as well as the many types of skincare ingredients and how to choose the appropriate one based on the adolescent's skin. Compared to the Pre-test, which was administered prior to the presenter's explanation of the topic, there was an increase in knowledge on the Post-test. Therefore, it can be inferred that participants gained knowledge from this activity's material and conversations, particularly in regards to the skincare material offered.